PATTERN OF ISLAMIC MORAL DEVELOPMENT FOR CHILDREN WITH SPECIAL NEEDS (BLIND) - Umar Sidiq; Nurul Aini (JIE (Journal of Islamic Education), 2019)
Blind is a person who has a disorder in his vision. A person's blindness is caused by endogenous factors such as hereditary, or due to exogenous factors, such as accidents, drugs and others. The main obstacle of a blind child is not working in his sense of vision. So that children with visual impairments, including children with special needs, are children who experience physical disorders that are different from normal children so that children with visual impairments need special education services and guidance so they can develop their potential as optimally as possible. This study aims to describe the foundation of guidance carried out on children with special needs (blind), as well as to describe aspects of coaching for children with special needs (blind). This study included qualitative research with a descriptive approach. Aisyiah Ponorogo Orphanage as a non-formal educational institution that carries out its duties and functions in learning and fostering children, including dealing specifically with children who have visual impairments. In such a long period of time, there are certainly many records and experiences in the development of blind children.